Charlemagne and Rome: Alcuin and the Epitaph of Pope Hadrian I. By Joanna Story. Oxford: Oxford University Press, 2023. 432 pp. 130 cloth - Collins, Samuel W. (Church history, 2024)
Charlemagne and Rome: Alcuin and the Epitaph of Pope Hadrian I. By Joanna Story. Oxford: Oxford University Press, 2023. 432 pp. 130 cloth. - Volume 93 Issue 3.